2020
DOI: 10.1186/s13065-020-00707-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of composition, antioxidant and antimicrobial activity of two adult edible insects from Tenebrionidae family

Abstract: In the case of Tenebrionidae family insects, studies focus on larval stage, leaving a lack of information regarding other stages. Therefore, this study was performed in order to understand the differences between the nutritional composition and the bioactivity of two species of this family in their adult stage, fed with a specific diet. Adult beetles of both species were defatted, lyophilized and protein extracted with buffer. Proximal and phytochemical analysis of the extracts of each insect were performed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…No studies on human subjects were available. Table 1 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) shows the studies investigating the in vitro antioxidant activity of edible insects and invertebrate fractions. Several methods were taken into account: the most used was the 1,1-diphenyl-2-picrylhydrazyl (DPPH), performed in 14 papers (7-15, 18-20, 23, 24), while 2,2 ′ -azino-bis(3ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing Abbreviations: 8-OHdG, 8-hydroxy-2 ′ -deoxyguanosine; ABTS, 2,2 ′ -azino-bis(3ethylbenzothiazoline-6-sulfonic acid); CAT, catalase; DPPH, 1,1-diphenyl-2picrylhydrazyl; CP, compound; FRAP, ferric reducing antioxidant power; GHG, greenhouse gas emissions; GPx, glutathione peroxidase; GST, glutathione Stransferase; LS, lipo-soluble extract; MDA, malondialdehyde; NO, nitric oxide; Nrf2, Nuclear factor erythroid 2-related factor; ORAC, oxygen radical absorbance capacity; PH, protein hydrolysates; RNS, reactive nitrogen species; ROS, reactive oxygen species; SAHR, scavenging activity on hydroxyl radicals; SOD, superoxide dismutase; SRSC, superoxide radical scavenging capacity; TAC, total antioxidant capacity; TEAC, Trolox equivalent antioxidant capacity; TOS, total oxidant status; WI, whole insect; WS, water-soluble extract.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…No studies on human subjects were available. Table 1 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) shows the studies investigating the in vitro antioxidant activity of edible insects and invertebrate fractions. Several methods were taken into account: the most used was the 1,1-diphenyl-2-picrylhydrazyl (DPPH), performed in 14 papers (7-15, 18-20, 23, 24), while 2,2 ′ -azino-bis(3ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing Abbreviations: 8-OHdG, 8-hydroxy-2 ′ -deoxyguanosine; ABTS, 2,2 ′ -azino-bis(3ethylbenzothiazoline-6-sulfonic acid); CAT, catalase; DPPH, 1,1-diphenyl-2picrylhydrazyl; CP, compound; FRAP, ferric reducing antioxidant power; GHG, greenhouse gas emissions; GPx, glutathione peroxidase; GST, glutathione Stransferase; LS, lipo-soluble extract; MDA, malondialdehyde; NO, nitric oxide; Nrf2, Nuclear factor erythroid 2-related factor; ORAC, oxygen radical absorbance capacity; PH, protein hydrolysates; RNS, reactive nitrogen species; ROS, reactive oxygen species; SAHR, scavenging activity on hydroxyl radicals; SOD, superoxide dismutase; SRSC, superoxide radical scavenging capacity; TAC, total antioxidant capacity; TEAC, Trolox equivalent antioxidant capacity; TOS, total oxidant status; WI, whole insect; WS, water-soluble extract.…”
Section: Search Strategymentioning
confidence: 99%
“…antioxidant power (FRAP) were utilized in 11 (6,7,10,11,13,14,16,17,19,20,22) and 8 studies (6, 10-12, 14, 15, 19, 21), respectively. Antioxidant activity was investigated also as scavenging activity against different radicals, metal ion chelating activity, reducing power, or, only for the paper of Sun et al (25), with β-carotene and linolenic acid bleaching tests.…”
Section: In Vitro Antioxidant Activities Of Edible Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the individual active components of CBTL are separated and tested for their anti-oxidation effects independently, Sun (2018) found that CBTL extract exhibited better effect presumably due to the synergistic effects of various active components in the CBTL extract. In contrast, the protein extract of Tenebrio molitor, Ulomoides dermestoides, and Bombyx mori exhibited high antioxidant activities in some edible insects (Baek et al, 2020;Flores et al, 2020). CBTL also contains high protein content, suggesting the peptides or amino acids to be antioxidant.…”
Section: Anti-oxidation Active Componentsmentioning
confidence: 94%
“…In sub-Saharan Africa, edible insects have been used as food because they are a good source of protein and essential fatty acids [ 19 , 20 , 21 ]. They are also high in micronutrients such as copper, iron, magnesium, manganese, phosphorus, selenium, and zinc, as well as vitamins such as riboflavin, pantothenic acid, biotin, folic acid, vitamin A, B complex, and C [ 22 , 23 ].…”
Section: Edible Insects In Africa and Their Microbiotamentioning
confidence: 99%